Changes in routes and proposals: case study of public transport on the UFAM campus in Manaus using GIS - Oliveira Neto, Thiago (2024)
Background: This article presents the main changes in the routes of public transportation buses that transport buses that transport students, civil servants and other professionals to the professionals to the UFAM campus in Manaus, using GIS tools. The study considered the routes taken by bus lines and users to access the university campus. campus and the important discussion on mobility and urban circulation. circulation. Methodology: Based on bibliographic and field surveys, it was identified that there were changes to the lines between 2012 and 2023, resulting from a process of reorganization of public transport in the capital of Amazonas. transportation in the capital of Amazonas, which made it difficult for people to access the campus. Considerations: Finally, three new connections were proposed between the UFAM campus and the city's main trunk line. the city's main trunk line, between the East Zone terminals and between the North Zone terminals. terminals in the North Zone, which are an area of urban expansion. area.